Isolation and Production of Human Monoclonal Antibody Proteins against a Toxocara canis Excretory–Secretory Recombinant Antigen - Zamrina Baharudeen; Rahmah Noordin; Lim Theam Soon; Dinesh Balachandra; Nor Suhada Anuar; Fatin Hamimi Mustafa; Anizah Rahumatullah (Pathogens, 2022)
Toxocariasis is a widespread zoonotic parasitic disease with a significant socioeconomic impact, particularly on underprivileged communities. Limitations of existing diagnostic tools and vague presenting symptoms may lead to misdiagnosis, thus underestimating the actual global impact of the disease. The present study describes the isolation and production of novel recombinant monoclonal antibodies against Toxocara canis recombinant TES-26 antigen (rTES-26) utilizing a human helminth scFv phage display library. The isolated antibody clones were characterized based on their gene sequences and binding characteristics. Three clones representing unique gene families (clone 48: IgHV3-LV1; clone 49: IgHV3-LV3; clone 50: IgHV6-LV3) were isolated, but only clones 48 and 49 showed successful insertion of the full-length scFv antibody sequence after sub-cloning. Both clones produced antibody proteins of good solubility and satisfactory yield and purity. Binding assays via Western blot and ELISA using rTES-26 and Toxocara canis native protein showed that both monoclonal antibodies were highly specific and sensitive to the target antigen. A preliminary antigen detection ELISA showed the diagnostic potential of the monoclonal antibody proteins. The proteins can also be useful in studying host–parasite interactions and therapeutic applications.